2010
DOI: 10.1073/pnas.0914503107
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody produced in plants efficiently treats West Nile virus infection in mice

Abstract: Over the past decade, West Nile virus (WNV) has spread to all 48 of the lower United States as well as to parts of Canada, Mexico, the Caribbean, and South America, with outbreaks of neuroinvasive disease occurring annually. At present, no therapeutic or vaccine is available for human use. Epidemics of WNV and other emerging infectious disease threats demand cost-efficient and scalable production technologies that can rapidly transfer effective therapeutics into the clinical setting. We have previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(192 citation statements)
references
References 35 publications
9
181
0
2
Order By: Relevance
“…The collective results the delivered DNA [3]. The ability to deliver vectors to a majority of the have demonstrated that this system is robust and drives high levels of target protein accumulation up to 1 mg per gram of leaf fresh weight (LFW), within 7 to 10 days after agroinfiltration [5,6,24,28,29]. This system retains the speed and expression amplification of viral vectors, while gaining the flexibility of nuclear gene expression.…”
Section: Vector Constructionmentioning
confidence: 99%
See 4 more Smart Citations
“…The collective results the delivered DNA [3]. The ability to deliver vectors to a majority of the have demonstrated that this system is robust and drives high levels of target protein accumulation up to 1 mg per gram of leaf fresh weight (LFW), within 7 to 10 days after agroinfiltration [5,6,24,28,29]. This system retains the speed and expression amplification of viral vectors, while gaining the flexibility of nuclear gene expression.…”
Section: Vector Constructionmentioning
confidence: 99%
“…Finally, this system integrates the posttranslational processing capacity of eukaryotic plant cells, for producing complex proteins. Along with others, our laboratory has expressed numerous proteins from small subunit vaccines to large immune complexes, with this system [5,6,28,29]. The collective results the delivered DNA [3].…”
Section: Vector Constructionmentioning
confidence: 99%
See 3 more Smart Citations